Thyroid disorders in subjects with Down syndrome: an update - Amr, Nermine H. (Acta Biomed, 2018)
Down syndrome (DS) is the commonest chromosomal disorder among live born infants. DS is associated with increased risk of endocrine abnormalities particularly thyroid gland disorders. The spectrum of thyroid dysfunction in patients with DS include congenital hypothyroidism, subclinical hypothyroidism, acquired hypothyroidism (autoimmune - non autoimmune), and hyperthyroidism. This review will focus on the characteristics of the different presentations of thyroid abnormalities in DS, screening and management recommendations. (www.actabiomedica.it)